2009
DOI: 10.1111/j.1398-9995.2009.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a pseudoallergen‐free diet on chronic spontaneous urticaria: a prospective trial

Abstract: Altogether the pseudoallergen-free diet is beneficial for one in three patients. The pseudoallergen-free diet is a safe, healthy and cost-free measure to identify patients with chronic spontaneous urticaria that will benefit from avoiding pseudoallergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 24 publications
4
69
0
8
Order By: Relevance
“…Therefore, higher or lower response rates to LPD may be due to different profiles of urticarial activity in these studies. Recent studies are more detailed about study designs, contents of diets, clinical evaluation criteria and analysis of the results [2,3,12,27]. Nevertheless, it is not possible to compare the response rates of these studies since there are not standardized criterion/criteria for defining ''response''.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, higher or lower response rates to LPD may be due to different profiles of urticarial activity in these studies. Recent studies are more detailed about study designs, contents of diets, clinical evaluation criteria and analysis of the results [2,3,12,27]. Nevertheless, it is not possible to compare the response rates of these studies since there are not standardized criterion/criteria for defining ''response''.…”
Section: Discussionmentioning
confidence: 99%
“…Bunselmeyer et al [2] administered a 5-week pseudoallergen-free diet, which caused improvement (reduction of severity of symptoms and increase in quality of life) in 68% of patients with CU. Last, Magerl et al [12] evaluated the response with improvement in urticarial activity score (with wheal and pruritus scores) and dermatology life quality index. 28% of patients were defined as strong and partial responders.…”
Section: Discussionmentioning
confidence: 99%
“…Besin katkı maddelerinin bazı hastalarda ürtikeri tetiklediği ve/ veya şiddetlendirdiği bilinmektedir (18,27). Kronik spontan ürtikerli hastaların katkı maddesi içermeyen diyetten fayda görmesi, gastrik mukozal permeabilitenin azalması gibi bir kolaylaştırıcı faktörün beraberinde olması ile açıklanmaktadır.…”
Section: Bulgularunclassified
“…Some studies have reported an association between CSU and food intolerance. Results of several intervention trials showed that the elimination of “pseudoal­lergens” from a patient’s diet can reduce the severity of CSU [1, 2]. Guidelines released by the European Academy of Allergy and Clinical Immunology (EAACI), the Global Allergy and Asthma European Network (GA 2 LEN), the European Dermatology Forum (EDF), and the World Allergy Organization (WAO) recommend that CSU patients consume a pseudoallergen-free diet for 3 weeks [3].…”
Section: Introductionmentioning
confidence: 99%